The Effect of Progressive Muscle Relaxation on Anxiety in Covid-19 Patients in Bandung - Herdiman, Herdiman; Fauzi, Deni Hamdan; Lindayani, Linlin (STIKep PPNI Jawa Barat, 2022)
Aims: Hospitalized patients with COVID-19 have been shown to experience high levels of anxiety, according to studies of their mental health, and yet these patients' states of mind have been shown to play a significant role in boosting the immune system during COVID-19 treatment. Purpose: The purpose of this study was to determine the effect of progressive muscle relaxation on anxiety in patients with COVID-19. Methods : The research method was a Quasi Experimental pre-test and post-test design with a control group. The sampling technique was Convenience Sampling with 40 samples which were divided into 20 samples as intervention group and 20 people as control group. Progressive muscle relaxation of 20-30 minutes twice a day for 5 days was only given to the intervention group. A pre-test and post-test using the Fear of COVID-19 Scale (FCV-19S) were implemented to measure anxiety. Data was collected and analyzed using Paired Sample T-test and ANCOVA. Results: showed a statistically significant change in anxiety levels from pre- to post-test for those in the intervention group, but no such change for those in the control group. The significance level for this test is 0.05, so the square root of the mean is 123,578 (F = 115,479) and the standard deviation is 0.000 (p 0.0001). In the intervention group, there is a statistically significant change in sleep quality scores between the pre- and post-test, while in the control group, there is no such change. Its square root is 112.118, its factor is 32.315, and its sign is 0.000 (p 0.05). Conclusions: The conclusion is that anxiety in patients with COVID-19 can be significantly reduced by administering progressive muscle relaxation.